Teachers' self-efficacy in dealing with students' online learning difficulties: A study of psychopragmatics in Indonesian language learning - Rohmadi, Muhammad; Sudaryanto, Memet (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Efficacy is teachers’ ability to strengthen their self-motivation to help solve learning problems faced by their students. In the learning process, psychopragmatic mastery is expected to strengthen the psychological condition of teachers and students through informative, manipulative, and persuasive sentences so that each student can optimize learning tools to help them achieve learning goals. During the pandemic, it is important to examine teachers’ self-efficacy and psychopragmatics mastery to support students in addressing their online learning difficulties. A qualitative study to investigate these issues was therefore conducted. Participants of this study were teachers from all over Indonesia, consisting of 350 middle and high school teachers. Data were collected through (1) a survey of teacher efficacy during online learning, (2) observations of the forms of efficacy built by the teachers during learning activities and outside the classroom, (3) interviews with the teachers to identify forms of efficacy used to shape students' learning fundamentals. It was found that the teachers tended to increase their efficacy through strong lesson planning. In addition, they often modified learning tools so that the multimedia used could foster enthusiasm and learning motivation for both themselves and the students. The teacher's efficacy in teaching is the key to analysis in psychopragmatic studies because data in the form of snippets of teacher speech can influence student motivation. Psychopragmatics in the teaching and learning process is not only considered the psychology of language that is practiced in learning the Indonesian language, but teachers also have internalized psychological reinforcement in the learning activity that has been planned, implemented, and assessed.